MELACAK SIGNIFIKANSI PENDIDIKAN MULTIKULTURAL ISLAM DI INDONESIA - Abd Aziz (Institut PTIQ Jakarta, 2020)
This research is a literature study related to Islamic multicultural education in Indonesia. Data collection was carried out through various sources that can be used in relation to the problems of Islamic multicultural education in Indonesia. In searching some literature using a search engine or maybe it is easier to index any type of document. For example, we use Google Scholar with a query containing Social Network clauses, of course the number of clauses will be generated with a list of related documents. The results show that education, whatever its form, must not lose its multicultural dimension, including religious and scientific education, because of the realities in life is essentially multidimensional. Likewise, humans themselves are essentially multidimensional creatures. Therefore, to overcome the existing humanitarian problems, there is no other way than to use a multidimensional approach. And, in it is multicultural education. Indonesia is a country that has ethnic diversity but has the same goal, namely towards a just, prosperous and prosperous society. Given this reality, it is important to develop multicultural education, which is an educational process that provides equal opportunities to all children of the nation regardless of treatment due to differences in ethnicity, culture and religion, which gives respect to diversity, and which gives equal rights to ethnic groups. minorities, in an effort to strengthen unity and integrity, national identity and the image of the nation in the eyes of the international community. In the case of multicultural education, schools must design the learning process, prepare curriculum and evaluation designs, and prepare teachers who have multicultural perceptions, attitudes and behaviors, so that they become parts that make a positive contribution to the development of multicultural attitudes of their students.